Research on double cylinder synchronous linear loading system based on sliding mode control with exponentially converging disturbance observer. Issue 1 (1st December 2022) - Yan, Yu; Fan, Yuanxun; Qiu, Haodong; Yang, Zeyu
Abstract : In the valve opening control of spacecraft, electro-hydraulic servo position-controlled loading is generally adopted. The nonlinear factors and uncertain interference in the loading system will affect the system accuracy. In order to improve the loading tracking accuracy and response speed, the nonlinear model of dual-channel valve-controlled symmetrical cylinder electro-hydraulic position servo loading system was established. A disturbance observer is used to estimate the unmodeled disturbances of the system, which is set up in combination with the sliding mode controller. Cross-coupling control is used to improve the synchronization accuracy of the two cylinders. The simulation study shows that the sliding mode control method based on exponentially converging disturbance observer can effectively improve the position tracking accuracy and synchronization control accuracy of the system compared with the traditional PID control. It has shorter response time and better anti-disturbance capability, which makes it have good control performance.